Dual‐State Emissive π‐Extended Salicylaldehyde Fluorophores: Synthesis, Photophysical Properties and First‐Principle Calculations. Issue 26 (13th July 2021) - Stoerkler, Timothée; Frath, Denis; Jacquemin, Denis; Massue, Julien; Ulrich, Gilles
Abstract: The search for simple, low‐cost, versatile, easily accessible, stimuli‐responsive, highly emissive molecular fluorophores emitting both in solution and in the solid‐state has prompted us to investigate the optical properties of a series of synthetically accessible salicylaldehyde derivatives possessing a π‐conjugated moiety at their 4‐position. These dyes are mainly known as synthetic intermediates but can also display sizeable Excited‐State Intramolecular Proton Transfer (ESIPT) fluorescence owing to the presence of a 6‐membered H‐bonded ring in their structure. The photophysical properties of these compounds have been studied in solution (multiple solvents) and in the solid‐state, as doped in PMMA films, KBr pellets or as powders leading to the observation of a pronounced fluorosolvatochromism. Emission wavelengths in the range 400–654 nm, along with photoluminescence quantum yields up to 76 % were recorded. Modification of the spacer (ethynyl, vinyl or direct connection) involved the π‐delocalization triggers major differences in terms of maximum emission wavelength and fluorescence quantum yields in the various media studied. All photophysical observations are rationalized by first‐principle calculations. Abstract : The synthesis and photophysical properties of a series of functionalized salicylaldehydes derivatives are reported. The compounds show strong fluorescence intensity in solution and in the solid state in various environments. The results are rationalized by ab initio calculations.